Industrial Relations in Emerging Economies The Quest for Inclusive Development - Hayter, Susan; Lee, Chang-Hee (Edward Elgar Publishing, 2018)
By examining the evolution of industrial relations institutions in the emerging economies of Brazil, China, India, South Africa and Turkey, the authors in this book assess the contribution of these institutions to inclusive development. Industrial Relations in Emerging Economies uses real-world examples to assess the relevance of the conceptual frameworks used to examine employment relations. The chapters focus on the evolution of industrial relations institutions and the role that these have played in periods of economic and political transition. They demonstrate that rather than acting as a constraint on development, trade unions can contribute to stability, security and equity. The contribution of industrial relations institutions to inclusive development nonetheless remains the subject of debate, viewed by some as increasingly irrelevant to the vast numbers of workers in the informal economy. The authors here, however, reveal a continuing demand for independent collective interest representation in labour relations, whether in the informal economy or in rapidly industrializing districts. This book will prove an interesting and stimulating read for students, academics and researchers in the fields of human resources, industrial relations, sociology and labour economics in addition to trade union researchers and policy-makers.